Appraisal of coral bleaching thresholds and thermal projections for the northern Red Sea refugia - Eladawy, Ahmed; Nakamura, Takashi; Shaltout, Mohamed; Mohammed, Asmaa; Nadaoka, Kazuo; Fox, Michael D.; Osman, Eslam O. (Frontiers in Marine Science, 2022)
Corals in the northern Red Sea exhibit high thermal tolerance despite the increasing heat stress. It is assumed that corals throughout the Red Sea have similar bleaching thresholds (32°C or higher), and hence greater bleaching tolerance of corals in the northern Red Sea region is likely due to lower ambient water temperatures (25–28°C) that remain well below the corals’ physiological maxima. Whether bleaching patterns across the Red Sea are independent of the local maximum monthly mean of seawater temperature and aligned with an assumed 32°C threshold has yet to be determined. Here, we used remotely sensed surface sea temperature data spanning 1982–2020 to model spatial distributions of Degree Heat Weeks across the Red Sea in relation to assumed coral thermal threshold values of 30, 31, and 32°C. We also used the Coupled Model Intercomparison Project Phase 5 model outputs to predict warming trends in the Red Sea under different greenhouse gas representative concentration pathways (RCPs). We show that applying 32°C thresholds dramatically reduces effective Degree Heat Weeks in the north, but not in central or southern Red Sea regions, a finding that is consistent with historical bleaching observations (1998–2020) throughout the Red Sea. Further, model predictions under the most extreme RCP8.5 scenario exhibited ~3°C warming by the end of the 21st century throughout the Red Sea with less pronounced warming for the northern Red Sea (2–2.5°C) compared to the central and southern regions (2.7–3.1°C).This warming rate will remain below the assumed thermal threshold for the northern Red Sea which should help this region to serve as refugia (i.e., maintaining favorable temperatures) for corals to persist for decades ahead. Together, our results support the notion that corals have similar thresholds throughout the Red Sea; hence, coral bleaching thresholds are independent of the local maximum monthly mean. Consequently, where regional warming projections suggest the northern Red Sea will not reach assumed bleaching thresholds (32°C) before the end of the 21st century, coral reefs in the northern region may be among the last standing against climate change.